Borrador de un esquema orgánico de los archivos diocesanos - Sastre Santos, Eutimio (Revista española de derecho canónico, 2012)
It provides the draft of the scheme of the diocesan archives to aid its better governance. The diocesan archive is the instrument of "good governance" of the administrative and historical record of the diocese. A physical person without memory ignores who he is and what he did; a sad situation that es like a juridical person without an archive or who governs unwisely. The Scheme provides related juridical materials as customarily presented: General Principle, Administration of the diocesan archives and technical management, Governance, Access, Property and Protection of the records and Diocesan Historical Archive, as cultural goods, as part of the Historical Patrimony Documents, and closes with the final Provisions. Before is the Preamble with a basic Bibliography. The draft divides the text into juridical forms: titels, chapters and articles, divides into paragraphs or numbers. Language is a weak part of the Treatment of the recors and the autor has tried to respect ther terms of the Code